Effects of plant growth regulators in heliconia ‘Red Opal’ - Castro, Ana Cecilia Ribeiro de; Hawerroth, Fernando José; Taniguchi, Carlos Alberto Kenji; Silva, Tiago Freitas; Soares, Nazaré Suziane (Ornamental Horticulture, 2016)
The objective of this study was to evaluate growth regulators with purpose of reducing the size of heliconia ‘Red Opal’ potted plants. The experiment was carried out in randomized block design with five treatments (trinexapac-ethyl and paclobutrazol at rates of 37.5 and 75.0 mg of active ingredient per pot and control without growth regulator) and five replicates. The treatments were applied 40 days after planting the rhizomes in pots filled with soil. Thirty and 150 days after the growth regulator application, plant height, number of leaves and shoots, petioles length and leaf area were evaluated. One year after planting the rhizomes in pots the number of inflorescence and leaves (leaves, sheathing leaf bases and inflorescences) and rhizomes (rhizomes and roots) dry mass were determined. Trinexapac-ethyl had no differences compared to the control in any of the variables evaluated. Paclobutrazol proved effective in reducing plant height, leaf area and petiole length and increase in number of leaves and shoots but the effect was temporary. Also, it did not affect the inflorescences production and leaves and rhizomes dry mass. Paclobutrazol is efficient to promote height reduction and to increase the number of shoots in heliconia ‘Red Opal’ potted plants without affect the inflorescence formation but its effects is temporary.